(untitled) (SAARC Journal of Agriculture, 2020)
Salicylic acid (SA) is endogenous naturally occurring plant growth hormone acting as an important signaling molecule adds tolerance against abiotic stress. A field experiment was conducted to assess the efficacy of exogenous application of SA on growth, yield and storage performances of onion during Rabi 2012-13, 2013-14 and 2014-15. The experiment was comprised of 6 different treatments of SA including control. Exogenous applications of all SA treatments significantly influenced plant growth and development. The treatment application of SA at 30 days after seed sowing and second spray at 30 days after transplanting and third spray at 60 days after transplanting performed superior in terms of growth, development and yield. Exogenous application of SA significantly influenced on thrips population and stemphylium blight disease incidence and intensity. The results also revealed that SA partially involved in post-harvest management of onion. SAARC J. Agri., 18(1):39-49 (2020)